2016
DOI: 10.1103/physreve.93.030601
|View full text |Cite
|
Sign up to set email alerts
|

Reentrant network formation in patchy colloidal mixtures under gravity

Abstract: We study a two-dimensional binary mixture of patchy colloids in sedimentation-diffusion equilibrium using Monte Carlo simulation and Wertheim's theory. By tuning the buoyant masses of the colloids we can control the gravity-induced sequence of fluid stacks of differing density and percolation properties. We find complex stacking sequences with up to four layers and reentrant network formation, consistently in simulations and theoretically using only the bulk phase diagram as input. Our theory applies to genera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…A gravitational field is, in general, unavoidable in sedimentation experiments, and might have a profound effect on colloidal mixtures 34 . For example, in a mixture of patchy colloids with two and three patches (all of the same type) gravity induces the formation of complex sequences in sedimentation-diffusionequilibrium such as the presence of re-entrant percolation 35 .…”
Section: Discussionmentioning
confidence: 99%
“…A gravitational field is, in general, unavoidable in sedimentation experiments, and might have a profound effect on colloidal mixtures 34 . For example, in a mixture of patchy colloids with two and three patches (all of the same type) gravity induces the formation of complex sequences in sedimentation-diffusionequilibrium such as the presence of re-entrant percolation 35 .…”
Section: Discussionmentioning
confidence: 99%
“…This results in additional gravity-induced phenomenology not present in bulk systems. Examples are denser particles floating on top of lighter colloids [7], a nematic layer sandwiched by isotropic layers in mixtures of platelets and spheres [8] and mixtures of thin and thick rods [9], and reentrant network formation in mixtures of patchy colloids [10]. It is also common to observe complex stacking sequences in sedimentation with three or more different layers, such as e.g., in mixtures of charged platelets and polymers [11], plate-plate binary systems [12], mixtures of spheres of different sizes [13], and colloidal rod-plate mixtures [14].…”
Section: Introductionmentioning
confidence: 99%
“…The percolation is only recovered for very high packing fractions. Previous studies of functionalized colloidal particles have reported also reentrant phenomena driven by, e.g., gravitational fields [33,34], competition between different energy scales [35][36][37], and patches activated by temperature [38].…”
Section: Discussionmentioning
confidence: 99%